Reforms of European Union biofuel policies - CGIAR Research Program on Policies, Institutions, and Markets (2019)
For the past ten years, IFPRI research – with support from PIM since 2012 – has informed the European Union debate on biofuels. The most recent piece of legislation on this topic is the 2018 Renewable Energy Directive, which will impact the USD 45 billion European biofuel market and is expected to reduce greenhouse gas emissions by about 13 million tons annually.